2020
DOI: 10.3846/jbem.2020.11758
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Performance of Colombian Banks by Hybrid Multicriteria Decision Making Methods

Abstract: The aim of the study in this paper is to show how the performance of banks can be evaluated by ranking them based on Balanced Scorecard (BSC) and Multicriteria Decision Making (MCDM) methods. Nowadays, assessing the performance of companies is a vital work for finding their weaknesses and strengths. The banking sector is an important area in the service sector. Many people want to know which bank performs best when entrusting their money to them. For assessing the performance of banks, BSC can be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…Moreover, the successful accomplishment of numerous business activities in pharmaceutical companies endures the paramount survival by deploying strategic conduct and establishing endogenous relationships among companies and a high-technology manufacturing strategy [49,59], translating not only "challenging," but even "grand challenging" situations, especially for the Islamic Republic of Iran. Unzipping this critical spectrum, this study presents a new paradigm of prioritizing manufacturing strategy essential factors of success via MCDM methods, so this decision-making plays a crucial role in reaching a "winwin" scenario through SWARA methods, which is an appropriate technique because specialists can openhandedly deliberate and verbalize their conclusions [101,[119][120][121]. It does not seem that individual conditions can do anything in apprehension of anticipated perceptions; therefore, the additional investigation can be appropriate for this merging procedure as a malleable method for other situations.…”
Section: Discussion and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the successful accomplishment of numerous business activities in pharmaceutical companies endures the paramount survival by deploying strategic conduct and establishing endogenous relationships among companies and a high-technology manufacturing strategy [49,59], translating not only "challenging," but even "grand challenging" situations, especially for the Islamic Republic of Iran. Unzipping this critical spectrum, this study presents a new paradigm of prioritizing manufacturing strategy essential factors of success via MCDM methods, so this decision-making plays a crucial role in reaching a "winwin" scenario through SWARA methods, which is an appropriate technique because specialists can openhandedly deliberate and verbalize their conclusions [101,[119][120][121]. It does not seem that individual conditions can do anything in apprehension of anticipated perceptions; therefore, the additional investigation can be appropriate for this merging procedure as a malleable method for other situations.…”
Section: Discussion and Contributionsmentioning
confidence: 99%
“…e merits of using ARAS method are that its logic concepts use simple mathematics and its computation is straightforward. is hybrid method is used in this research for these reasons [31,101].…”
Section: Research Gapmentioning
confidence: 99%
“…According to the findings, it was concluded that private sector banks should increase their performance by investing in income-generating areas. Yazdi et al [61] used Balance Scorecard and MCDM techniques for the performance ranking of Colombian banks. In the study, in which the step-wise weight assessment ratio analysis (SWARA) method was used for the weighting of the decision matrix, the performance indicators were listed by the weighted aggregate product assessment (WASPAS) method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The fuzzy VIKOR approach was then used to rank the alternatives. Yazdi et al (2020) conducted an evaluation of Abstract Banks play a crucial role as financial intermediaries in advancing economies. Increasing market share is a top priority for all banks in today's fiercely competitive market.…”
Section: Introductionmentioning
confidence: 99%